Analisis User Experience Pada Website Streaming Video (Studi Kasus: Youtube dan VLIVE) - Risma Ismulia Rahmi; Retno Indah Rokhmawati; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
According to a survey of 82 respondents, only 12 respondents prefer to use VLIVE, while the rest choose to stream using Youtube. This study will provide user experience comparison analysis on VLIVE and Youtube websites subjectively and objectively. The objective analysis will be tested using scenario based on parameters: task completed, error during task performance, time per completed task and number of clicks during task completion. The subjective analysis was conducted by interviews of respondents based on user experience honeycomb factor. There are two groups of respondents: VLIVE groups and Youtube groups, each have 3 respondents. As a result of the objective analysis, this studies reported that Youtube is more effective and easy to use compared with VLIVE based on the parameters of task completed. Based on the parameters of error during task performance, VLIVE can be regarded as a website that is more effective and easier to use. While VLIVE more efficient based on parameters of time per completed task and parameter number of clicks during task completion. The result of subjective analysis of user experience factors is: useful: both websites have different content categorization, usable: both websites are easy to use, desirable: the content of VLIVE is more exclusive, findable: The features is contained in the VLIVE and Youtube websites only different on the provided feature name, accesable: required internet connection to access, and credible: VLIVE can login using social media account, while Youtube uses email. This study also conducted each of the characteristics both the advantages and disadvantages.